Empowering Women Through Financial Literacy in Rajasthan - Arora, B; Sharma, S; Pahwa, M.S (International Journal of Computer Sciences and Engineering, 2025)
The paper unfolds the dearth and bottlenecks of microfinancecredit facilities to women in Rajasthan. The study focuses on the financial literacy among women in rural area as compared to urban women. The contribution in GDP of rural women is exorbitant which indicates potential growth but literature shows lack of proper financial support to women has affected their contribution in GDP and has led to lower contribution in the economic growth of rural population in Rajasthan. The Paper focuses on the level of financial literacy among the rural woman of Rajasthan